(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Objectives: The main objective of this study is to determine the advanced program to develop scientific research skills by using Google Scholar tools among students in education and Art College at Tabuk University. Methods: It is a retrospective cross-sectional study of a specific batch of students from the education and art collage at Tabuk University. Result: There are statistically significant differences on the scale of scientific research skills using the tools of the scientific researcher from Google in pre-measurement and post-measurement after the application. Conclusion: The study showed that the advanced program to develop scientific research skills by using Google Scholar tools among students of the university was statistically significant differences on the scale of scientific research skills using the tools of the scientific researcher from Google scholar tools.